Recovery of Vanadium (V) Oxyanions by a Magnetic Macroporous Copolymer Nanocomposite Sorbent - Ljiljana Suručić (MDPI AG, 2021)
An amino-functionalized magnetic macroporous copolymer of glycidyl methacrylate (GM) and ethylene glycol (E) dimethacrylate (m-poly(GME)-deta) was synthesized, fully characterized, and used to investigate the adsorption of vanadium (V) oxyanions from aqueous solutions (Ci = 0.5 mM) in a batch system at room temperature (298 K). Pseudo-first-order (PFO), pseudo-second-order (PSO), Elovich, and intra-particle diffusion (IPD) models were used to analyze the kinetic data. The study showed that sorption is rapid, i.e., the sorption half-time is approximately one minute. Initially, the sorption process primarily involved surface sorbent particles, and it was best described by the PSO model. However, after saturation of the surface active sites is attained, the sorption rate decreases significantly because of limitations of the diffusion rate, which is then primarily controlled by the IPD process. The sorption process is favorable in the pH range of 3–6 due to the strong electrostatic interactions between the absorption centers of copolymer and vanadium (V) oxyanions. In the stated pH range, deta absorption centers with two and three protonated N atoms are in equilibrium as studied by quantum chemical modeling. Among V(V) species present in diluted aqueous media, the adsorption of H2VO4− ions dominates.